Accessibility and competency development: student experiences of a simulated practicum in postgraduate psychology training - Jaeva Shelley; Adam J. Rock; Nicola Schutte; Suzanne M. Cosh; Kylie Rice (Australian Journal of Psychology, 2025)
Objective Practica are an integral component of postgraduate psychology training. Traditional face-to-face practica, however, have experienced challenges such as struggles to ensure students are exposed to a broad range of common mental health conditions, limited practicum availability, and student barriers to completing psychology practica, such as geographical location. Fully simulated practica represent a novel training approach that may address the challenges identified in face-to-face practica. The present study aimed to explore the perspectives and experiences of postgraduate professional psychology students completing a fully simulated practicum.Method Seven semi-structured focus groups were conducted, in which students (N = 30) shared their perspectives of competency development within a simulated practicum, benefits, and challenges, of a simulated practicum. Reflexive thematic analysis was utilised to analyse the data and two thematic maps were developed to represent the findings.Results The first thematic map “Evaluating My Competence in a Simulated Environment” explored students’ perspectives on increased competence as a result of the practicum. Students reported that their competence increased across a range of domains but that they may not have developed skills for responding to challenging client scenarios and expressed concerns that completing a simulated practicum might influence others' perceptions of their competence. The second thematic map “There are Unique Benefits and Challenges to a Simulated Environment” outlined safety, accessibility, the capacity to target and scaffold competency development, and peer interaction as unique strengths of a simulated learning environment. Students also identified challenges of skills practice within a simulated environment, such as inaccurate depictions of clinical presentations due to student actors’ lack of familiarity with different diagnoses, and a struggle to understand the expectations of their role in a new learning environment.Conclusions The results of the present study suggest that a fully simulated practicum may increase accessibility of psychology training programs and address a range of challenges present in face-to-face practica.